Prediction of time of delivery using cervical length measurement in women with threatened preterm labor. (18th August 2021) - Ho, Nicole; Liu, Cathy; Nguyen, Anh; Lehner, Christoph; Amoako, Akwasi; Sekar, Renuka
Abstract: Objective: To evaluate the use of transvaginal (TV) sonographic cervical length (CL) measurement alone in predicting time of delivery in women who present in threatened preterm labor. Methods: A retrospective cohort study at Royal Brisbane and Women's Hospital of all women who presented between 22 weeks and 0 days and 35 weeks and six-day gestation in threatened preterm labor and were admitted for ongoing management including a TV sonographic CL measure. The accuracy of CL for predicting time of delivery was compared between women with a short cervix (CL  < 25 mm) and those with a normal cervix (CL ≥25 mm). The predictive accuracy of CL for spontaneous preterm delivery was analyzed with different outcome-specific thresholds. Results: One hundred and forty-six women with threatened preterm labor met the inclusion criteria; of which 74 (50.7%) had a short cervix and 72 (49.3%) had a normal cervix. The group with short cervix were more likely to deliver prematurely before 37-week gestation, as well as a shorter time interval between initial presentation and delivery and delivery within 14 days from presentation ( p  = .0002, p  = .0001, and p  = .0001, respectively). Similarly, with respect to the area under the receiver operator characteristic curves, CL measurement was found to be significant for time of delivery before or after 37 weeks ( p  < .0001), preterm delivery before 34 ( p  =  .0003) and 31 ( p  <  .0001) weeks; and preterm delivery within 14 days from presentation ( p  < .0001). Cervical length measurement has a high negative predictive value ranging from 94.9 to 97.1% depending on the different CL threshold used. Conclusions: Cervical length measurement at the time of presentation was significantly associated with the risk of preterm delivery in women presenting with threatened preterm labor and a short cervix. Cervical length measurement was also helpful in predicting time of delivery within 14 days from presentation. The negative predictive value and predictive accuracy of CL as a single measure were of significance.